Hantavirus–Leptospira coinfections in small mammals from central Germany. (22nd February 2021) - Jeske, K.; Jacob, J.; Drewes, S.; Pfeffer, M.; Heckel, G.; Ulrich, R. G.; Imholt, C.
Abstract: European orthohantaviruses (Puumala orthohantavirus (PUUV); Dobrava-Belgrade orthohantavirus (DOBV), genotype Kurkino; Tula orthohantavirus (TULV)), and Leptospira spp. are small mammal-associated zoonotic pathogens that cause diseases with potentially similar symptoms in humans. We investigated the frequency of Leptospira spp. and hantavirus single and double infections in small mammals from 22 sites in Thuringia, central Germany, during 2017. TULV infections were detected at 18 of 22 sites (mean prevalence 13.8%, 93/674). PUUV infections were detected at four of 22 sites (mean prevalence 1.5%, 7/471), and respective PUUV sequences formed a novel phylogenetic clade, but DOBV infections were not detected at all. Leptospira infections were detected at 21 of 22 sites with the highest overall prevalence in field voles ( Microtus agrestis ) with 54.5% (6/11) and common voles ( Microtus arvalis ) with 30.3% (205/676). Leptospira –hantavirus coinfections were found in 6.6% (44/671) of common voles but only in two of 395 bank voles. TULV and Leptospira coinfection probability in common voles was driven by individual (age) and population-level factors. Coinfections seemed to be particularly associated with sites where Leptospira spp. prevalence exceeded 35%. Future investigations should evaluate public health consequences of this strong spatial clustering of coinfections.